2006
DOI: 10.1109/tps.2006.872446
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of excited Xe atoms density in alternating current plasma display panel by means of laser absorption spectroscopy

Abstract: The exited Xe atoms in the 1s 5 metastable state and the 1s 4 resonance state across the two sustaining electrode have been monitored in a micro-discharge cell of alternating current plasma display panels (PDPs) by laser absorption spectroscopy. In this study, it is found that the maximum excited xenon density is 5 4 10 12 cm 3 in the 1s 5 metastable state and 1 2 10 12 cm 3 in the 1s 4 resonance state for the PDP cell with gap distance of 150 m and width of 350 m under the fixed gas pressure of 350 torr and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There were some examples in which the high electric field was achieved by the modification of cell design. 10,31,32 However, those designs are not easy to apply in real PDPs because of the complication in fabrication. Figure 4 shows the change in E/p distribution with time for each case.…”
Section: B Spatiotemporal Profilesmentioning
confidence: 99%
“…There were some examples in which the high electric field was achieved by the modification of cell design. 10,31,32 However, those designs are not easy to apply in real PDPs because of the complication in fabrication. Figure 4 shows the change in E/p distribution with time for each case.…”
Section: B Spatiotemporal Profilesmentioning
confidence: 99%
“…The profile of the applied voltage shows a square pulse with a driving frequency of 42 kHz and a duty ratio of 25%. Laser absorption spectroscopy 16,17 was used to measure the atom density N m in a metastable state of Xe ‫ء‬ ͑ 3 P 2 ͒. Excited xenon atoms in the metastable state were measured using a near-infrared laser of 823 nm.…”
Section: Fast Oscillatory Behavior Of the Excited Xenon Density In Thmentioning
confidence: 99%
“…It is noted that the VUV 173 nm emitted from the excited molecular dimers still increases with the increasing xenon mole fractions, because the dimers scales linearly with the Xe density. It is observed that the excited Xe atom's density for the 1s 4 resonant state is usually three times smaller than that for the 1s 5 metastable state [12], [13] even though the peak intensity of resonant 147 nm are much stronger than that of 173 nm [7]. Here, it is also noted for the high Xe mole fractions above ∼10% that the integrated intensity over the continuum emission wavelength for the 173 nm from the molecular dimers Xe * 2 is much bigger than that of 147 nm for the 1s 4 resonant Xe atoms, which gives direct influence on the luminous efficiency.…”
Section: Spatiotemporal Behavior Of Excited Xenon-atom Density In Accmentioning
confidence: 99%
“…Here, it is also noted for the high Xe mole fractions above ∼10% that the integrated intensity over the continuum emission wavelength for the 173 nm from the molecular dimers Xe * 2 is much bigger than that of 147 nm for the 1s 4 resonant Xe atoms, which gives direct influence on the luminous efficiency. Hence, we particularly investigated the spatiotemporal behavior of the excited Xe-atom density of the 1s 5 metastable state without taking account of 0093-3813/$25.00 © 2008 IEEE the 1s 4 resonant atoms in this paper according to the various Xe mole fractions of 4%, 7%, 10%, and 15% to Ne gas by the laser-absorption spectroscopy [13]- [15]. The excited Xe-atom density in the 1s 5 metastable state plays a dominant role in luminous efficiency.…”
Section: Spatiotemporal Behavior Of Excited Xenon-atom Density In Accmentioning
confidence: 99%
See 1 more Smart Citation